Social support, depression, anxiety and stress among breast cancer patients receiving chemotherapy in Hospital Universiti Sains Malaysia - Rokhman, Nik Nor Izwana (Universiti Sains Malaysia, 2024)
Depressive disorder or depression is a common mental disorder that involves a depressed mood or loss of pleasure or interest in activities for long periods of time. Social support is an important variable in buffering the effects of depression, anxiety and stress. This study aims to assess the level of social support, depression, anxiety and stress among breast cancer patients receiving chemotherapy. A cross-sectional study was conducted in a Day-Care Oncology Unit Hospital Universiti Sains Malaysia from January to March 2024. A total of 124 respondents were conveniently selected and data was collected using a self-administered questionnaire. The mean age of the respondents was 53 years old (SD=10.62), with ages ranging between 28 to 76 years old. Pearson Correlation was used to determine the correlation between social support, depression, anxiety and stress. The result shows that levels of depression, anxiety and stress were 7.3%, 9.7% and 1.6% respectively and the majority of them have high levels of social support. The study revealed a significant inverse correlation between social support and both anxiety (r = -0.181, p = 0.004) and stress (r = -0.215, p = 0.017). In conclusion, social support is negatively correlated with depression, anxiety, and stress. Therefore, education that provides information about these psychological conditions and emphasizes the importance of social support is necessary to reduce their impact.